Does IVF-ET Procedure Increase the Pregnancy Rates in Women Underwent Laparoscopic Endometriosis Surgery? - Gürhan Güney; Aytekin Tokmak; Ali İrfan Güzel; Turgut Var; Esra İşçi; Ali Sertaç Batıoğlu (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: To evaluate pregnancy rates in women who underwent In Vitro Fertilization-Embryo Transfer (IVF-ET) following laparoscopic endometriosis surgery and to assess the success of IVF-ET.